Seismic evaluation of 1940s asymmetric wood-frame building using conventional measurements and high-definition laser scanning. - Mosalam, Khalid M.
This study presents results from shake table experiments of a wood-frame building conducted at the University of California, Berkeley. A 13.5-ft × 19.5-ft two-story wood-frame building representing San Francisco 1940s design of a residential building with a garage space on the first story (house-over-garage) was tested. The test building was subjected to scaled ground motion based on Los Gatos record from Loma Prieta 1989 earthquake. The strong motion time history was scaled to match design spectra of a site in Richmond district of San Francisco. The test results demonstrated the seismic vulnerability of the test building due to soft story mechanism and significant twisting when shaken in two horizontal directions. In addition to conventional instrumentation for measuring acceleration and position of selected points of the test building, high-definition laser scanning technology was employed to assess global and local anomalies of the building after the shake table tests. The analysis conducted in this study showed very good correlation between conventional data recorded from position transducers and the laser scans. These laser scans expanded limits of conventional data at discrete points and allowed analyzing the whole building after shaking.
Keywords: House-over-garage.; Laser scan; Shake table; Soft story; Torsion; Wood-frame.